Artificial Intelligence In Strategic Decision Making - Zein, Afrizal (STEBIS Bina Mandiri, 2025)
Artificial Intelligence (AI) has become an increasingly important tool in strategic decision-making across a range of industry sectors. In an increasingly complex and uncertain world, AI offers the ability to analyze large amounts of data, identify patterns, and provide recommendations that can improve the quality of decisions made by managers and organizational leaders. The use of AI in strategic decision-making not only increases efficiency, but also enables more accurate planning and responsiveness to market changes. This article discusses various applications of artificial intelligence in supporting strategic decision-making, including in the areas of market forecasting, resource optimization, and long-term planning. In addition, this article also reviews the challenges and limitations in implementing AI, such as data quality, model reliability, and potential ethical risks. While AI can speed up and improve the decision-making process, it is important to still involve human perspectives in the final decision-making process to ensure that the policies taken still consider social, ethical, and environmental factors. By understanding the role and potential of AI in strategic decision-making, organizations can adopt this technology more effectively, increase competitiveness, and optimize future business outcomes.